Genetic effects for controlling stripe rust (Puccinia striiformis f. sp. tritici) resistance in wheat through joint segregation analysis - Kalim Ullah; Naqib Ullah Khan; Rozina Gul; Samrin Gul; Mohammad Irfaq Khan; Imdad Ullah Khan (Acta Scientiarum. Agronomy, 2016)
Mixed inheritance analysis using joint segregation analysis (JSA) for stripe rust (Puccinia striiformis f. sp. tritici) resistance was carried out in six basic populations (P1, F1, P2, BC1, BC2 and F2) of four wheat crosses (Hashim-08 × LU-26, Farid-06 × Shafaq, Parula × Blue Silver, TD-1 × D-97603) during crop season 2009 to 2012. Genes controlling stripe rust resistance were assessed by using area under disease progress curve (AUDPC). The AUDPC was controlled by mixed two additive-dominant-epistatic major genes plus additive-dominant-epistasis of polygenes in cross Hashim-08 × LU-26 (model E), while in Farid-06 × Shafaq, it was controlled by mixed two major additive-dominant genes plus additive-dominant polygenes (model E-2). In cross Parula × Blue Silver, the AUDPC was managed by additive, dominance and epistasis of two major genes (model B-1), however, it was controlled by mixed one major gene and additive dominant polygenes in cross TD-1 × D-97603 (model D-1). Genetic variation and heritability was higher in major genes than polygene for all the crosses showing that AUDPC was mainly controlled by major genes. The genetic behavior of the AUDPC revealed that stripe rust resistance was controlled by mixed interaction of one to two major genes plus polygenes.